Politeness Strategy in Students Lingua to Their Lecturers Via WhatsApp at Information Technology Department of Technical Faculty Universitas Bhayangkara Jakarta Raya - Hafizah Hafizah (Indonesian Language and Literature Education Study Program and LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2019)
The purpose of this research is to know politeness strategy used by students to communicate with lecturers through short messages WA (WhatsApp). The data source in this research is the speech from students to lecturers. The research method used is a qualitative descriptive method through three stages, namely data collection, data analysis, and presentation of the results of the analysis. The results showed that students used the politeness strategies of Brown and Levinson when communicating with their lecturers via text messages WA (WhatsApp). The words